Identification of Data-Based Public Administration Governance Strategies: Opportunities and Challenges - Afridian Wirahadi Ahmad; Mohamad Muspawi; Andre Ariesmansyah; Mochamad Heru Riza Chakim; Hefri Yodiansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This article aimed to identify a data-based public administration governance strategy regarding the opportunities and challenges in today's digital era. The authors believe that choosing a strategy in managing data technology-based public administration services is part of the success of organizations, including the government, in serving public partnerships. So to ensure the truth of this article's questions, we have collected field study evidence to study in-depth so that we can get answers to this royal question with convincing and high quality. So that the chest can be said to be a finding, first, our data has been carefully studied, involving a coding system for data interpretation and drawing conclusions under a phenomenological approach, namely an effort to search for the broadest possible data to get answers that are concise and clear. The data sources that we focus on are scientific publications, journals, and other literature documents made public between 2010 and 2021 to find the data easily. Based on the study and discussion, we conclude that the effort to identify the right strategy for the government in managing public records is to provide data services on the internet, considering that all human activities, both business and public services, have been increasingly popularly adopted from the old way of talking about big data technology. It is hoped that this finding will become a significant input in improving studies on data-based public services.